PSV-B-19 Dietary choline supplementation increases transmethylation through the one-carbon cycle in overweight cats. (8th October 2021) - Rankovic, Alexandra; Godfrey, Hannah; Grant, Caitlin E; Shoveller, Anna-Kate; Bakovic, Marica; Kirby, Gordon; Verbrugghe, Adronie
Abstract: The objective of this study was to determine the dose-response relationship between dietary choline intake and one-carbon cycle activity in overweight cats at maintenance energy requirements. This study was approved by the University of Guelph Animal Care Committee (AUP#4118). Overweight (body condition score:≥6/9) adult male neutered cats (n = 14) received each of five choline chloride doses individually for three weeks in a 5x5 latin square design. Doses were based on body weight (BW) and the daily recommended allowance (RA) for choline for adult cats (63 mg/kg BW 0.67 ). Doses were: 2xRA (126 mg/kg BW 0.67 ), 4xRA (252 mg/kg BW 0.67 ), 6xRA (378 mg/kg BW 0.67 ), 8xRA (504 mg/kg BW 0.67 ), and control (no additional choline). Choline was administered onto the commercial extruded cat food (3620 mg choline/kg diet), given once a day at maintenance energy requirements (130 kcal/kg BW 0.4 ). Fasted serum samples were analyzed for metabolomics through quantitative nuclear magnetic resonance (NMR) spectroscopy and direct infusion mass spectrometry (DI-MS) at the end of each period. Data was analyzed using proc GLIMMIX in SAS, with group and period as the random effects, and dose as the fixed effect. Statistical significance was considered at P < 0.05. Tukey's post-hoc test was performed to assess multiple comparisons. Choline at 6x and 8x RA appears to increase transmethylation through the one-carbon cycle, as suggested by increased serum betaine, dimethylglycine (DMG) and methionine (P < 0.05). Carnitine, methylated by s-adenosylmethionine (SAM), increased (P < 0.05). Serine and threonine, precursors for the biosynthesis of homocysteine, appear to have been spared (P < 0.05). Supplemental dietary choline (6x and 8xRA) may be beneficial for overweight cats, as it may increase activity of the one-carbon cycle and methyl status; which are necessary for hepatic function. To better understand the impact of choline on methylation reactions, the quantification of specific proteins, gene expression and/or conversion rates is required.